2018
DOI: 10.1159/000489483
|View full text |Cite
|
Sign up to set email alerts
|

CD56 Expression Is an Important Prognostic Factor in Multiple Myeloma Even with Bortezomib Induction

Abstract: Objectives: In this retrospective study, we evaluated the impact of CD56, CD117, and CD28 expression on clinical characteristics and survival in newly diagnosed myeloma patients treated with bortezomib-based induction therapy. Methods: We analyzed 110 myeloma patients. Immunophenotype was determined using panels consisting of CD19/CD38/CD45/CD56/CD138 and CD20, CD28, and CD117 were used additionally. All samples were tested for recurrent chromosomal aberrations. Results: CD56, CD117, and CD28 expression rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 22 publications
4
30
1
Order By: Relevance
“…In conclusion, CD56 may indeed be associated with prognosis and remains one of the leading myeloma markers, as Skerget et al [4] reported. We recommend assessing CD56 as well as other myeloma markers in the clinical practice setting.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In conclusion, CD56 may indeed be associated with prognosis and remains one of the leading myeloma markers, as Skerget et al [4] reported. We recommend assessing CD56 as well as other myeloma markers in the clinical practice setting.…”
mentioning
confidence: 59%
“…In the last issue of Acta Haematologica, Skerget et al [4] reported that a lack of CD56 is associated with worse progression-free survival in patients with R-ISS stage 2 MM treated by a bortezomib-based regimen, but not with worse overall survival. Although their results corroborated the results of previous studies, patients with R-ISS stage 2 comprise approximately 60% of MM patients and, in their study, the patient group was further stratified by CD56 expression [5].…”
mentioning
confidence: 99%
“…CD56 is strongly expressed by malignant plasma cells in 70% of myeloma patients and represents a potential immunotherapy target. CD56 is also expressed at lower levels on normal tissue types (including neuronal cells, NK cells, and parts of activated T cells) (41). In vitro cytotoxicity tests show that CD56 CAR-T cells have a significant lysis effect on myeloma cell lines, and can effectively eradicate tumor cells in MM mice at a dose of 5×10 6 (18).…”
Section: Cd56mentioning
confidence: 99%
“…Eighty percent of the cells were positive for Ki-67. 11,12 The bony defect was covered with a titanium mesh, and soft tissue was reconstructed using a latissimus dorsi muscle free flap covered by a split-thickness skin graft. Anastomoses were performed in an end-to-end fashion between the thoracodorsal vessels and the left superficial temporal vessels.…”
Section: Case Presentationmentioning
confidence: 99%
“…The tumor cells were positive for CD56, CD79a, CD138, and lambda light chains, and negative for CD20, IgM, and kappa light chains. Eighty percent of the cells were positive for Ki‐67 11,12 …”
Section: Case Presentationmentioning
confidence: 99%